Lack of OxyR and KatG Results in Extreme Susceptibility of Francisella tularensis LVS to Oxidative Stress and Marked Attenuation In vivo - Honn, Marie; Lindgren, Helena; Bharath, Gurram K.; Sjöstedt, Anders (Frontiers in Cellular and Infection Microbiology, 2017)
Francisella tularensis is an intracellular bacterium and as such is expected to encounter a continuous attack by reactive oxygen species (ROS) in its intracellular habitat and efficiently coping with oxidative stress is therefore essential for its survival. The oxidative stress response system of F. tularensis is complex and includes multiple antioxidant enzymes and pathways, including the transcriptional regulator OxyR and the H2O2-decomposing enzyme catalase, encoded by katG. The latter is regulated by QxyR. A deletion of either of these genes, however, does not severely compromise the virulence of F. tularensis and we hypothesized that if the bacterium would be deficient of both catalase and OxyR, then the oxidative defense and virulence of F. tularensis would become severely hampered. To test this hypothesis, we generated a double deletion mutant, ΔoxyR/ΔkatG, of F. tularensis LVS and compared its phenotype to the parental LVS strain and the corresponding single deletion mutants. In accordance with the hypothesis, ΔoxyR/ΔkatG was distinctly more susceptible than ΔoxyR and ΔkatG to H2O2, ONOO-, and O2-, moreover, it hardly grew in mouse-derived BMDM or in mice, whereas ΔkatG and ΔoxyR grew as well as F. tularensis LVS in BMDM and exhibited only slight attenuation in mice. Altogether, the results demonstrate the importance of catalase and OxyR for a robust oxidative stress defense system and that they act cooperatively. The lack of both functions render F. tularensis severely crippled to handle oxidative stress and also much attenuated for intracellular growth and virulence.